Inhibition of the invasive plant Ambrosia trifida by Sigesbeckia glabrescens extracts - Lijuan Yin; Guangzhong Zhang; Haoyu Zhao; Yuxin Zhang; Jiaozi Wangchen; Fanghao Wan; Bo Liu; Wanqiang Qian (Ecotoxicology and Environmental Safety)
Ambrosia trifida is an invasive weed that destroys the local ecological environment, and causes a reduction in population diversity and grassland decline. The evolution of herbicide resistance has also increased the difficulty of managing A. trifida, so interspecific plant competition based on allelopathy has been used as an effective and sustainable ecological alternative. However, how to control A. trifida through interspecific competition and the underlying mechanisms are unclear. Here, we found that extracts from both the roots and leaves of the medicinal plant Sigesbeckia glabrescens suppressed the growth of A. trifida by reducing the plant height and biomass. The decrease in biomass may be explained by disruption of carbon and nitrogen metabolism. These disruptions are due to a significant decrease in the expression of genes related to nitrate absorption and transport in roots and a significant decrease in the expression of key genes related to photosynthesis and carbon fixation. Consequently, genes involved in sucrose synthesis are downregulated. In addition, increases in H2O2 content and respiratory burst oxidase homologue (RbohD) gene expression suggested that A. trifida underwent oxidative stress caused by reactive oxygen species (ROS) bursts, resulting in apoptosis due to the significant upregulation of key genes associated with apoptotic pathways. Furthermore, we identified three main allelochemicals, coumarin, ferulic acid, and 5-aminolevulinic acid (5-ALA), in S. glabrescens extracts and revealed that the combination of these three compounds could suppress the growth of A. trifida seedlings. The phenotypes and transcriptome profiles of the seedlings treated with these chemicals were the same as those of the seedlings treated with the S. glabrescens extracts. Taken together, the results of this study revealed the mechanism underlying the toxic effects of S. glabrescens on A. trifida, providing a theoretical basis for the use of interspecific plant competition for invasive weed control and further application of S. glabrescens allelochemicals in weed management.